Landscapes of violence: women surviving family violence in regional and rural Victoria - Amanda George (2014)
In this research, family violence survivors have identified issues and barriers they have encountered, and have provided suggestions in regards to how both the criminal justice system and the broader Victorian community might assist survivors and help prevent family violence. Overview This project combines the findings of two studies undertaken by the Centre for Rural and Regional Law and Justice. Drawing on and extending the findings in Women's experience of surviving family violence and accessing the Magistrate's court in Geelong, Victoria (2013), this report extends the research in terms of geographic areas, issues covered and range of participants. It examines the experiences of, and outcomes for, women survivors of family violence in regional and rural Victoria, considering their contact with, and perceptions of, government agencies (including Victoria Police, the Victorian Magistrate's courts and the Department of Human Services) as well as private and community advocates (legal services, women's services and family violence services) and healthcare professionals. Through this research, survivors have identified issues and barriers they have encountered in escaping family violence, and have provided suggestions in regards to how both the criminal justice system and the broader Victorian community might assist survivors and help prevent family violence. As well as being informed by survivors, this publication includes insights provided by government and non-government practitioners and organisations who have offered their views on this report's key findings and recommendations. In addition to the generous contributions of these participants, this report utilises relevant data and emerging research in an effort to identify best practice responses to family violence; improve access to justice, support and safety; and protect and promote women's rights and entitlements